Guidelines for superficial venous thrombosis - de Almeida, Marcelo José; Guillaumon, Ana Terezinha; Miquelin, Daniel; Joviliano, Edwaldo Edner; Hafner, Ludvig; Sobreira, Marcone Lima [UNESP]; Geiger, Martin Andreas; Moura, Regina [UNESP]; Raymundo, Selma; Yoshida, Winston Bonnetti [UNESP] (FapUNIFESP (SciELO), 2019)
Superficial venous thrombosis (SVT) or superficial thrombophlebitis is characterized by thrombi within superficial veins, with partial involvement or occlusion of the lumen and inflammatory reaction along the course of the vein. Clinical diagnosis tends to be straightforward, but supplementary tests and examinations are needed to confirm thrombosis extension and possible thromboembolic complications. SVT can be associated with deep venous thrombosis in 6 to 40% of cases, with asymptomatic pulmonary embolism (PE) in 20 to 33%, and with symptomatic PE in 2 to 13%. Despite the morbidity and complications, there are currently no Brazilian guidelines for SVT. These guidelines cover the most important issues related to SVT definition, terminology, and etiology, and set out recommendations for diagnosis and treatment.
Diretrizes de conceito, diagnóstico e tratamento da trombose venosa superficial
Keywords: Clinical practice guidelines; Phlebitis; Pulmonary embolism; Thrombophlebitis; Veins; Venous thrombosis